Virtualization of Museums as an Element of the Modern Education of Young Tourist Specialists - Tetiana Zubekhina; Olesia Dyshko; Liudmyla Matviichuk; Yuliia Dashchuk (Jan Długosz University in Częstochowa, 2024)
The article justifies the expediency of training specialists in the field of tourism by means of museum virtualization. It is emphasized that the development of modern information technologies shapes the theory and practice of electronic education. Various definitions of the term 'virtual museum', types of virtual museums, criteria for their classification, reasons for popularity, and the history of their development are partly presented. It is emphasized that virtual museums are characterized by structural and functional diversity and are of great importance for the development of cultural tourism. The results of a student survey are presented, confirming the feasibility of using virtual tours in the educational process: it is interesting for students, increases the level of mastery of professionally-oriented knowledge and skills, promotes the development of a sustained in-depth interest in communication with museum objects, the development of creative abilities, the formation of media competences. It is shown that virtual museums provide an opportunity to fill the learning process with new interesting content through the use of modern Internet technologies.